Selected Studies in Biodiversity 2018
DOI: 10.5772/intechopen.76606
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Harvesting of Marula (Sclerocarya Birrea) in Swaziland: A Quest for Sustainability

Abstract: All across sub-Saharan Africa rural communities, and especially women, are harvesting natural products for income generation purposes. In recent times, the degradation of ecosystems in terms of loss of biodiversity has become a major concern, especially when the harvesting of the species in question has become commercialized as is the case of marula harvesting in Swaziland. This chapter reports on some of the findings of a study conducted to explore the impact of commercial harvesting on the future availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…This supports previous studies that explained that S. birrea is a tree well-known to local people in southern Africa [2]. Some studies [2,3,5,7,8] documented the importance of this species in the lives of people; hence, S. birrea is considered a keystone species [9,21]. For instance, local communities enjoy eating its fruit and nuts, but also use it to a certain extent for fuelwood and medicinal purposes.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This supports previous studies that explained that S. birrea is a tree well-known to local people in southern Africa [2]. Some studies [2,3,5,7,8] documented the importance of this species in the lives of people; hence, S. birrea is considered a keystone species [9,21]. For instance, local communities enjoy eating its fruit and nuts, but also use it to a certain extent for fuelwood and medicinal purposes.…”
Section: Discussionsupporting
confidence: 86%
“…Other scholars have similarly found that marula trees play a significant role in the lives and livelihoods of local communities [3,5,8]. However, unlike in other areas such as Swaziland and Bushbuckridge in South Africa [3,17,21], marula products have not been commercialised in Ha-Mashau and Ha-Mashamba villages. In the present study, the majority of respondents indicated that marula trees do not have an economic impact on the lives and livelihoods of people, because marula products (e.g., marula beer) are enjoyed for free when there are social gatherings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sclerocarya b. birrea subspecies caffra is the most widespread and most researched in southern and southwestern African parts of the continent (Ojewole et al, 2010;Seloana et al, 2017;Nndwammbi et al, 2018;Sinthumule & Mzamani, 2019). S. birrea caffra is a keystone African savanna tree species with high ecological, commercial and cultural value (Helm et al, 2011;Murye & Pelser, 2018). It is an abundant fruit bearing tree which plays a significant role in the lives of both humans and animals in southern African ecosystems (Hall & O'brien, 2002;Gouwakinnou et al, 2011;Mocheki et al, 2018;Sinthumule & Mzamani, 2019).…”
mentioning
confidence: 99%
“…In countries where it is found, the marula species has long formed an integral part of rural communities' livelihoods, culture and spirituality (Wynberg et al, 2003). It is known to support the lives of rural families as they harvest its timber and non-timber products (Wynberg & Laird, 2007;Gouwakinnou et al, 2011;Murye & Pelser, 2018). The marula species is used to generate income, medicine and for nutrition (Thiong'o et al, 2000;Shackleton & Shackleton, 2005).…”
mentioning
confidence: 99%